Pengaruh Profesional Dosen Terhadap Kualitas Pembelajaran Dosen Agama Islam Di Fakultas Keguruan Ilmu Pendidikan Universitas Pattimura - Husaini, Husaini (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2017)
This aims to knows : 1) whether the professional competence of lecturers affect on learning quality of islamic lecturers,Â  2) how much the influenceof pedagogical and professional competence of lecturers on the learning quality of Islamic lecturers.The research method with the quantitative approach through the observation and distribution of a questionnaire as a data collection tool, the total sample of 94 students who had attended the study of Islamic education in teachering and education facultyin Pattimura University. The study are : 1) professional competence possessed by Islamic lecturersgive the influence on learning qualityof Islamic lecturers, 2) the effect of the competence of Islamic lecturers on learning quality ofIslamic lecturers, include a) contributions relative based on a questionnaire that gives response "adequate" amount 68,36% of professional competence, and also effective contribution based on questionnaires responded "good / 49,93% of professional competence.